Edukasi Dagusibu Antibiotik Bagi Masyarakat Kelurahan Sambutan Samarinda - Risa Supriningrum; Ghina Adhilla; Dwi Ajeng (Jurnal Abdi Masyarakat Kita, 2023)
Efforts to increase public knowledge and understanding about the use of antibiotics need to be made. This is because many people assume that antibiotic drugs are drugs to cure various diseases. This growing phenomenon among the community is motivated by the lack of knowledge related to the use of antibiotics. Education on Dagusibu (Get, Use, Store and Dispose) antibiotics is expected to increase people's understanding of how to get, use, store and dispose of antibiotics and can implement it in everyday life, especially in the immediate family environment. This community service activity by lecturers of the College of Health Sciences was carried out in Sambutan Village, Sambutan District, Samarinda, East Kalimantan. The counseling participants were PKK mothers and Posyandu cadres who were expected to disseminate the information we had conveyed to the surrounding community. Keywords: Dagusibu, antibiotics, Sambutan Village